2010
DOI: 10.1176/appi.ajp.2009.09010105
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Depressive Symptoms in 711 Patients With Bipolar Disorder Evaluated Prospectively in the Stanley Foundation Bipolar Treatment Outcome Network

Abstract: Bipolar patients spend a substantial proportion of their time ill. Significant gender differences exist, with women spending a greater proportion of their visits in the depressive pole. This finding appears to be related to the corresponding differences in rates of rapid cycling and anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 47 publications
1
61
1
2
Order By: Relevance
“…Males are often less likely to seek help for depressive episodes compared to females, and therefore may not present to the services early until a manic episode necessitates help. It is noteworthy that another study from USA too reports that bipolar females were more likely to have a depressive onset of BAD (24).…”
Section: Discussionmentioning
confidence: 93%
“…Males are often less likely to seek help for depressive episodes compared to females, and therefore may not present to the services early until a manic episode necessitates help. It is noteworthy that another study from USA too reports that bipolar females were more likely to have a depressive onset of BAD (24).…”
Section: Discussionmentioning
confidence: 93%
“…This is partially responsible for the varying prevalence rates among studies and the confl icting opinions between authors. Any anxiety disorder is reported to be present in 42-93 % of patients during lifetime and in almost 11-70 % cross-sectionally (Young et al 2013 ;Tamam and Ozpoyraz 2002 ;Altshuler et al 2010 ;Zutshi et al 2006 ;Simon et al 2004b ;Kawa et al 2005 ;Kessler et al 1997 ;Levander et al 2007 ;Nakagawa et al 2008 ;Goldstein and Levitt 2008 ;Schaffer et al 2006 ;Otto et al 2006 ;Nery-Fernandes et al 2009 ;Mantere et al 2006Mantere et al , 2010Henry et al 2003 ;Freeman et al 2002 ;Dittmann et al 2002 ;Das 2013 ;Cosoff and Hafner 1998 ;Ciapparelli et al 2007 ;Bellani et al 2012 ;McElroy et al 2001 ;Boylan et al 2004 ;Szadoczky et al 1998 ;Weber et al 2011 ;Azorin et al 2009 ). Up to half of these BD patients with comorbid anxiety manifest at least two anxiety disorders (Henry et al 2003 ).…”
Section: Comorbid Anxietymentioning
confidence: 99%
“…In BD patients, panic disorder is reported to have a cross-sectional prevalence of 2.3-62.5 % and a lifetime prevalence of 2.9-56.5 % (Vieta et al 2001 ;Schaffer et al 2006 ;Young et al 1993Young et al , 2013Tamam and Ozpoyraz 2002 ;Altshuler et al 2010 ;Zutshi et al 2006 ;Simon et al 2004b ;Kawa et al 2005 ;Kessler et al 1994Kessler et al , 1997Levander et al 2007 ;Nakagawa et al 2008 ;Goldstein and Levitt 2008 ;Rihmer et al 2001 ;Azorin et al 2009 ;Pini et al 1997Pini et al , 2003Otto et al 2006 ;Okan Ibiloglu and Caykoylu 2011 ;Mula et al 2008a ;Henry et al 2003 ;Dilsaver et al 1997Dilsaver et al , 2008Slama et al 2004 ;Dell'Osso et al 2011 ;Craig et al 2002 ;Cosoff and Hafner 1998 ;Ciapparelli et al 2007 ;Mantere et al 2006 ;McElroy et al 2001 ;Robins and Regier 1991 ;Chen and Dilsaver 1995 ;Bellani et al 2012 ;Boylan et al 2004 ;Coryell et al 2009 ;Szadoczky et al 1998 ). The phase of the disorder plays an important role; panic is virtually absent in purely manic patients and present in more than 80 % of mixed or depressive patients (Dilsaver and Chen 2003 ).…”
Section: Comorbid Panic Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that disease often starts with a manic episode in men and with a depressive episode in women (4,5). Although women reported to experience higher number and more frequent depressive episodes (4) and reported to have more cycles and mixed episodes (6)(7)(8)(9), there are studies showing that these frequencies resemble at both genders (3,10,11).…”
mentioning
confidence: 99%